25. PERUSAHAAN MILITER SWASTA DALAM SENGKETA BERSENJATA INTERNASIONAL: STUDI KASUS OPERATION ENDURING FREEDOM DI AFGHANISTAN TAHUN 2001-2010 - Syarifah, Claudia; Utomo, Tri Cahyo; Paramasatya, Satwika (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
The end of the Cold War marked the beginning of New War, where the war is no longerbetween state actors, but among the non-state actors, such as private military companies(PMC). PMC was established to accommodate the Cold War’s veterans and the soldierwho are out of contract or civilians to serve as mercenaries. This study is an initial attemptto investigate the use of PMC in Afghanistan and how it effects on Operation EnduringFreedom, the effort of the warlords in doing military privatization for the sake of financialinterest, and how PMC could be actively involved in international armed conflicts andweaken the monopoly of force which is only owned by the state. The method of this studyis descriptive and tend to use inductive analysis approach. Process and meaning morehighlighted in this qualitative study. Marxism is used as foundation of the theory to guidethis study in accordance with the facts available. This study shows how power, money,using democracy and freedom as disguise, and underlying motives is carrying out militaryactivities in some countries. It also presents an overview of the benefits which PMCoffered and the huge damages such offers had violated human rights.